Developing a Biology E-Module Based on Pjbl-Steam Model to Improve Students’ Collaboration Skills - Wiji Agustin; Murni Sapta Sari; Suhadi Suhadi; Siti Juwariyah (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
Digital inequality and the pandemic have exacerbated the learning crisis, caused some learning loss, also fostered students’ individualistic attitude, which resulted in poor collaboration skills. Furthermore, the models and approaches in the teaching material activities have not reflected the stages that encouraged the practice to enhance collaboration skills. Meanwhile, collaboration skills can be trained and developed by selecting the right teaching materials that are integrated with appropriate learning models. The development of PjBL-STEAM-based E-Module is believed to be able to improve students' collaboration skills. This study used a quasi-experimental design with basic random sampling. There were two study groups: the experimental and the control groups. The instruments used in this study were a self-assessment questionnaire measuring students’ collaboration skills and teachers’ observation sheets that aligned with the collaboration skill indicators. ANCOVA test was used to analyze the data. The findings showed that the E-Module has no significant effect on students' collaboration skills (α=0,213), while the covariates indicated some factors that significantly affect the improvement of students’ collaboration skills (α=0,004). The validation results of the PjBL-STEAM-based E-Module suggested that it is highly valuable to implement in the teaching and learning process.